Designing Supply Chain Performance Measurement Using SCOR and AHP in an Indonesian Packaged Drinking Water Company - Nurullaily Kartika; Bima Karismanda Diantoro (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to develop an appropriate Supply Chain performance measurement design for a packaged drinking water company (Company X) using the Supply Chain Operations Reference (SCOR) model. Design/methodology/approach – The Supply Chain Operations Reference (SCOR) model was used to develop key performance indicators (KPIs) related to supply chain performance measurement, The identified Key Performance Indicators (KPIs) were validated and weighted by three experts directly involved in the company’s supply chain activities, namely the Head of Candal and Warehouse Unit, the Head of Production, Maintenance and Laboratory Unit, and the Quality Control and Laboratory Staff, while the Analytical Hierarchy Process (AHP) method was applied to determine the weight of each KPI. Findings/Results – The study produced 35 KPIs consisting of 6 Plan process KPIs, 8 Source process KPIs, 9 Make process KPIs, 5 Deliver process KPIs, 6 Return process KPIs, and 1 Enable process KPI. The AHP weighting results indicate that the Return activity has the highest priority among the six supply chain activities, with a weight value of 0.362. Originality/Value – The study provides a Supply Chain performance measurement design for Company X by integrating the SCOR model and AHP method and identifies the Return activity as the most important supply chain activity.